Asuhan Keperawatan Medikal Bedah Pada Pasien Tn.S Dengan Tuberkulosis Paru Diruang Muzdalifah Rumah Sakit Aisyiyah Pariaman - Mai Reza Ardita Putri; Mike Asmaria; Debby Silvia Dewi; Hilma Yessi (CV. ITTC INDONESIA, 2026)
Pulmonary tuberculosis remains a health problem and is the second leading cause of death after Covid-19, with 10.6 million deaths reported globally in 2024. Indonesia ranks second with a pulmonary tuberculosis burden of 1,060,000 cases. In West Sumatra, 7,942 cases were recorded, while Pariaman City reported 62 cases. Locally, Rumah Sakit Aisyiyah Pariaman experienced an increase in the number of cases from 61 in 2023 to 104 in 2024.The purpose of this case study was to provide nursing care for patients with pulmonary tuberculosis in the Muzdalifah inpatient ward of Rumah Sakit Aisyiyah Pariaman. The method used was a case study conducted over five days, from February 10 to February 14, 2026, in the Muzdalifah ward of Rumah Sakit Aisyiyah Pariaman. The approach used was the nursing process, which included assessment, nursing diagnosis, intervention, implementation, and evaluation, with one patient diagnosed with pulmonary tuberculosis as the research subject.The results showed eight nursing diagnoses: ineffective airway clearance, impaired gas exchange, nutritional deficit, risk of infection, hyperthermia, acute pain, disturbed sleep pattern, and activity intolerance. Nursing implementations provided included airway management, oxygen therapy, nutritional management, infection prevention, hyperthermia management, pain management, sleep support, energy management, and health education.The evaluation conducted over five days showed that the nursing problems were resolved, and the patient was allowed to return home. Patients are advised to comply with treatment recommendations, maintain personal and environmental hygiene, avoid smoking, consume nutritious food, and routinely attend health facility check-ups to optimize the healing process and prevent transmission to others.